Pengaruh Kompensasi, Pengembangan Karir dan Spesifikasi Kerja Terhadap Motivasi Kerja Pegawai - Avanti, Anastasia; Siregar, A.R. Hasfianda; Lubis, Puspa Anriyani; Nasution, Achyad; Subhan, Abdu; Wasesa, Supar; Safrida, Safrida; Supriadi, Supriadi (Journal of Management and Economics Research, 2024)
This study aims to determine the Effect of compensation, career devlopment and work specifications partially and simultaneously on the employees work motivation in the Kantor Wilayah DJP Sumatera Utara I. The study was conducted at the Kantor Wilayah DJP Sumatera Utara I Jalan Sukamulia No. 17A Medan, with a population of 146 people, and a study sample. of 59 people. The data analysis technique used is multiple regression analysis using the IMB Statistics computer program for Product and Service Solution (SPSS) version 24. Based on the analysis results obtained compensation have a positive and significant effect on the employees work motivation of the Kantor Wilayah DJP Sumatera Utara I, this is supported by the results of t count analysis > t-table (2,867 > 2,004) at n = 59 at 95% significance level. Career devlopment has a not effect on the employees work motivation of the Primary Tax Service Office of Medan Timur, this is supported by an analysis of t count > t-table (3,331 > 2,004) at n = 59 at 95% significance level. Work specifications has a effect on the employees work motivation of the Kantor Wilayah DJP Sumatera Utara I, this is supported by an analysis of t count >-table (3,778 > 2,004) at n = 59 with a significant level of 95%. Value of F-count> F table (49,000 > 2,78) This states that together (multiple) there are positive and significant effects of compensation, career devlopment and work specifications on the employees work motivation of employees of the Kantor Wilayah DJP Sumatera Utara I. Thus the hypothesis proposed is accepted by the truth.